2009
DOI: 10.1002/adma.200803321
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Luminescent Switching in a [Eu(SiW10MoO39)2]13−‐Agarose Composite Film by Photosensitive Intramolecular Energy Transfer

Abstract: Transparent, flexible, self‐supporting EuSiWMo/agarose composite films are fabricated by a combination of hydrogel chemistry and a casting technique, and present reversible, high‐contrast luminescence photoswitching modulated by inorganic photochromic components through intramolecular resonance‐energy transfer. Two‐dimensional recording employing the luminescence as read‐out signals is accomplished in this novel recording medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 41 publications
3
57
0
1
Order By: Relevance
“…It had been reported from the crystal structure that the EuSiWMo was just like a dumbbell with a size of 1−2 nm. 28,39 So the bigger dots (2.70 nm) were the aggregative EuSiWMo, and the smaller dots were the disperse ones, which was consistent with the lifetime results of 30.0 μM EuSiWMo.…”
Section: Langmuirsupporting
confidence: 89%
“…It had been reported from the crystal structure that the EuSiWMo was just like a dumbbell with a size of 1−2 nm. 28,39 So the bigger dots (2.70 nm) were the aggregative EuSiWMo, and the smaller dots were the disperse ones, which was consistent with the lifetime results of 30.0 μM EuSiWMo.…”
Section: Langmuirsupporting
confidence: 89%
“…The combined analytical data confirmed that our synthetic strategy afforded POM-polymer conjugates TBA 7 …”
supporting
confidence: 79%
“…Our concept will provide chemists with a new tool to design POMs whose solubility is reversibly controllable through an external stimulus. POM-polymer TBA 7 . Extensive MS analysis was used to monitor the chain-functionalization steps and to confirm the formation of the hybrid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations